A Study of Assessment of Maternal Health Service Utilization in Rural Area of Surat District by Multi Indicator Cluster Survey - Hitesh Shah; Binita Desai; Vipul Chaudhari; S L Kantharia (National Journal of Community Medicine, 2013)
Introduction: Multi Indicator Cluster Survey (MICS) method is popular for assessment of health service coverage.